Acupuncture versus medical treatment for migraine and muscle tension headaches. Issue 4 (April 1984) - Loh, L; Nathan, P W; Schott, G D; Zilkha, K J
Abstract : In 48 patients with chronic migraine and muscle tension headaches, a comparison was made between a prophylactic course of acupuncture and of medical treatment. It was intended that all patients should have 3 months with both forms of treatment, but 19 were unwilling to change from one form of prophylaxis to the other. Twenty-four of 41 patients improved on acupuncture, the improvement being very marked in nine; nine of 36 patients improved on medical treatment, the improvement being marked in three. Of the 29 patients who changed from one form of treatment to the other, a larger proportion preferred acupuncture to medical treatment. A beneficial response to acupuncture was more likely when the patient had local tender muscular points. The presence of depressive features did not preclude satisfactory treatment with acupuncture. No major side effects were encountered with acupuncture.